1997
DOI: 10.1002/(sici)1097-0142(19971215)80:12<2321::aid-cncr14>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

The national cancer data base report on patterns of childhood cancers in the United States

Abstract: The authors concluded that the number of brain tumors of benign and uncertain behavior being diagnosed were significant enough in number that they should be included in regional and national cancer registries that report data for clinical purposes. They further concluded that for reasons of data inclusion and institutional coverage, the NCDB will be an important data base for pediatric cancers that will warrant increased use by pediatric investigators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
94
0
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(105 citation statements)
references
References 9 publications
7
94
0
4
Order By: Relevance
“…The incidence in the United Kingdom and the United States is ϳ1 in 7000 live births, and there is slight sex predominance in most series with a male-to-female ratio of 1.2:1. The disease accounts for 15% of all childhood cancer deaths, indicating the poor prognosis of many of the tumors (2)(3)(4). Children with stage 1, 2, or 4 s disease, or presenting in the first year of life have a good prognosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence in the United Kingdom and the United States is ϳ1 in 7000 live births, and there is slight sex predominance in most series with a male-to-female ratio of 1.2:1. The disease accounts for 15% of all childhood cancer deaths, indicating the poor prognosis of many of the tumors (2)(3)(4). Children with stage 1, 2, or 4 s disease, or presenting in the first year of life have a good prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, children (Ն1 year of age) with stage 3 and 4 disease have 3-year survival rates of 50% and 15%, respectively. Most children present over the age of 1 year with metastatic (stage 4) disease; this group has an overall survival of 10 -20% (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Malignant ovarian neoplasms account for only 1% of all childhood malignancies. 13 One literature review found no cases of pulmonary embolism occurring from a thrombosed vein. 14 Furthermore, it is reported that adnexal torsion patients underwent detorsion without oophorectomy and there were no patient (n=102) in this study had clinical signs of thromboembolism.…”
Section: Discussionmentioning
confidence: 99%
“…15 Somemore, necrotic-appearing ovaries demonstrate follicular activity on sonography weeks after conservative management. 5,13 Furthermore, the rate of malignancy in paediatric cases of ovarian torsion is low (1%). …”
Section: Discussionmentioning
confidence: 99%
“…Neuroblastoma is the most common extracranial solid tumor of childhood, accounting for 7-10% of all childhood malignancies (1,2). Most patients present with metastatic disease and have a poor prognosis (2,3).…”
Section: Introductionmentioning
confidence: 99%